Experimental protocol designed to employ Nd:YAG laser surgery for anterior chamber glaucoma detection via UBM. Issue 8 (20th March 2022) - Ali, Saba Ghazanfar; Ali, Riaz; Sheng, Bin; Chen, Yan; Li, Huating; Yang, Po; Li, Ping; Jung, Younhyun; Zhu, Fang; Lu, Ping; Kim, Jinman
Abstract: Angle closure glaucoma leads to fluid deposition in eye, and intraocular pressure occurs that damage the optic nerve, causes blindness and vision loss. Anterior chamber (AC) evaluation is imperative for determining the risk of angle‐closure. Previously, techniques were dependent on either Pentacam–Scheimpflug that interprets poor visual information, anterior segment optical coherence tomography is injurious to intercede opaque optical structures. Therefore, in this paper, an experimental protocol is designed for detailed disease analysis based on IBM SPSS statistics via ultrasound biomicroscopy which is superior in evaluating deep structures; first, the affected parameter for AC is analysed, and afterwards the direction that needs laser surgery is explored. Experiments are conducted on large‐scale clinical studies from an affiliated hospital in Shanghai, China. The dataset comprised 600 AC images in five directions of 60 subjects. The mean with standard deviation for anterior open distance is 0.15879 ± ± 0.096779 mm, 0.15863 ± ± 0.081435 mm, and anterior chamber angle is 18.749 ± ± 08.0315 ∘ ^° , 18.741 ± ± 08.3889 ∘ ^° for left and right eye respectively. It is found that anterior chamber angle in the downside of the AC is wider than the upside. However, this decision is partly based on the narrowest part of the angle to widen the depth of the direction and eliminate pupil block.